Yabancılık içeren arabuluculuk usulü ve bağlayıcılığı hakkında düşünceler - PÜRSELİM ARNİNG, HATİCE SELİN (My University, 2014)
The Turkish Mediation Act came into force on the 07th June 2012. It is a modern Act that was prepared in detail. The Turkish Mediation Act is also applicable to foreign conflicts according to its Art. 1. However, the Act contains only one article that governs such conflicts. Because of that, several important issues, like the recognition and enforcement of foreign mediation decisions as well as the language of the mediation proceedings, are still not explicitly regulated by law. In this article we analyse these issues by comparing Turkish law with the laws and regulations of other countries and organisations.

6325 sayılı Arabuluculuk Kanunu, 7.6.2012 tarihinde kabul edilmiştir. Kanun, modern ve detaylı bir düzenlemeye sahiptir. Kanunun 1. maddesinde, yabancılık içeren ihtilaflarda da bu Kanun’un uygulanacağı düzenlenmiştir. Kanun, yabancılık unsurunu tek bir madde ile düzenlemiş; ancak yabancı arabuluculuk kararlarının nasıl tanınıp tenfiz edileceğine veya görüşme de tercüman bulunup bulunmaması gibi konulara değinmemiştir. Çalışmamızda, mukayeseli hukuk dikkat alınarak bu hususlara genel olarak yer verilmeye çalışılmıştır.
Keywords: Sosyal ve Beşeri Bilimler; Hukuk; Devletler Özel Hukuku; Social Sciences and Humanities; Law; International Private Law; Sosyal Bilimler (SOC); Sosyal Bilimler Genel; HUKUK; Social Sciences (SOC); SOCIAL SCIENCES, GENERAL; LAW; Hukuk; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities; Mediation; Directive 2008/52/EC of the European Parliament and of the Council; German Mediation Law; ICC Mediation Rules; Mediation Rules of The German Institution of Arbitration; Arabuluculuk; 2008/52 sayılı Avrupa Parlamentosu ve Konseyi Yönergesi; Alman Arabuluculuk Kanunu; MTO arabuluculuk kuralları; Alman Tahkim Kurumu arabuluculuk kuralları